1998
DOI: 10.1073/pnas.95.6.3172
|View full text |Cite
|
Sign up to set email alerts
|

Functional anatomy of musical processing in listeners with absolute pitch and relative pitch

Abstract: We used both structural and functional brain imaging techniques to investigate the neural basis of absolute pitch (AP), a specialized skill present in some musicians. By using positron emission tomography, we measured cerebral blood f low during the presentation of musical tones to AP possessors and to control musicians without AP. Listening to musical tones resulted in similar patterns of increased cerebral blood f low in auditory cortical areas in both groups, as expected. The AP group also demonstrated acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
245
1
7

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(272 citation statements)
references
References 28 publications
19
245
1
7
Order By: Relevance
“…Additionally, we performed a variant of the conjunction analysis introduced by Price and Friston (1997) to determine which areas of activity were common to both the contrast of interest in this experiment and the tone perception condition among AP subjects in the PET experiment of Zatorre et al (1998). Briefly, this consists of performing a logical "AND" operation on all suprathreshold voxels existing in both the t statistic image of the tones Ϫ noise contrast in AP subjects from Zatorre et al (1998) and the t statistic image of the S2 chords Ϫ noise Ϫ S1 chords Ϫ noise contrast in this study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, we performed a variant of the conjunction analysis introduced by Price and Friston (1997) to determine which areas of activity were common to both the contrast of interest in this experiment and the tone perception condition among AP subjects in the PET experiment of Zatorre et al (1998). Briefly, this consists of performing a logical "AND" operation on all suprathreshold voxels existing in both the t statistic image of the tones Ϫ noise contrast in AP subjects from Zatorre et al (1998) and the t statistic image of the S2 chords Ϫ noise Ϫ S1 chords Ϫ noise contrast in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Although it seems likely that early and intensive musical training is necessary to develop absolute pitch (AP), these do not seem to be sufficient conditions, and the factors, genetic or otherwise, that interact with this training to dispose the individual to the acquisition of AP are still very much in question (Takeuchi and Hulse, 1993;Baharloo et al, 1998;Zatorre, 2003). A considerable amount of research has delved into various behavioral aspects of AP (Takeuchi and Hulse, 1993;Ward, 1999), but relatively few studies have investigated its neural correlates (Klein et al, 1984;Hantz et al, 1992;Wayman et al, 1992;Zatorre et al, 1998;Keenan et al, 2001). Electrophysiological studies using eventrelated potential techniques Wayman et al, 1992), for instance, have mainly shown a reduced P300 component among AP musicians in auditory oddball paradigms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors conclude that AP possessors may compute the size of the musical interval by knowing what the individual notes are, rather than by maintaining pitch in working memory. 14 It has been suggested that some AP possessors do not learn to develop relative pitch in its fullness, because they have learned to rely on AP in their musical activities. 11 Perhaps, then, some AP possessors try to perform interval recognition tasks using the RP strategy, but their comparatively poor sense of RP leads to poorer performance than possessors of RP alone.…”
Section: Does It Make You a Better Musician?mentioning
confidence: 99%